2021
DOI: 10.1159/000520235
|View full text |Cite|
|
Sign up to set email alerts
|

Similarities and Differences between COVID-19-Associated Nephropathy and HIV-Associated Nephropathy

Abstract: Kidney disease is a major complication of viral infection, which can cause both acute and chronic kidney diseases via different mechanisms such as immune-mediated injury, kidney cell injury from a direct viral infection, systemic effects, and antiviral drug-induced nephrotoxicity. HIV-associated nephropathy (HIVAN), characterized by collapsing focal segmental glomerulosclerosis (cFSGS), has been described 2 decades ago as a major complication of acquired-immunodeficiency syndrome. The pathogenesis of HIVAN has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 102 publications
(142 reference statements)
0
8
0
Order By: Relevance
“…In addition, the podocytes may proliferate to form a pseudo-crescentic structure [ 27 ]. HIVAN occurs mainly in African Americans with apolipoprotein L1 (APOL1) risk alleles and is a leading cause of ESRD in African Americans [ 3 ]. Disease expression and renal complications, and subsequent kidney injury risk require two APOL1 risk alleles.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the podocytes may proliferate to form a pseudo-crescentic structure [ 27 ]. HIVAN occurs mainly in African Americans with apolipoprotein L1 (APOL1) risk alleles and is a leading cause of ESRD in African Americans [ 3 ]. Disease expression and renal complications, and subsequent kidney injury risk require two APOL1 risk alleles.…”
Section: Reviewmentioning
confidence: 99%
“…A year later (1982), the same disease entity was diagnosed in Europe, and it was named AIDS by the Center for Disease Control (CDC) [ 2 ]. Since the first diagnosed case, about 79.3 million (55.9-110 million) have been infected with the virus [ 3 ], while over 25 million people have died already [ 4 ]. In addition, about two million new cases are diagnosed annually [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, Transient Receptor Potential Canonical Channel 6 (TRPC6), as an ion channel in podocytes, can directly be activated by ANGII, which leads to proteinuria [13,25]. The most common COVID-19-related renal complications are including acute tubular injury (ATI), collapsing glomerulopathy, thrombotic microangiopathy, complement activation, and IL-6-induced renal vascular permeability [13,17]. Therefore, the kidney injury leads to: (i) hypoxia-induced acute tubular necrosis with high level of creatinine, (ii) collapsing focal segmental glomerulosclerosis (cFSGS) together with hematuria, which are common in patients with APOL1 alleles, (iii) direct viral tropism of renal tissue with high levels of micro-or macro-albuminuria, and (iv) hemodynamic changes mediated by endothelitis along with electrolyte imbalance [26].…”
Section: Renal Manifestationsmentioning
confidence: 99%
“…Next, Lan and colleagues explored the protective effects of quercetin, a flavonoid purified from traditional Chinese medicine, in renal injury induced by the SARS-CoV-2 N protein. 7 As aging and diabetes are two comorbidities of COVID-19-associated nephropathy, 9 the authors tested the therapeutic effects of quercetin in aged mice with diabetes and showed that quercetin could attenuate the renal injury caused by the SARS-CoV-2 N protein. Mechanistically, quercetin can block the binding of the N protein and Smad3, hence lifting the cell-cycle arrest and reducing renal tubular cell necrosis.…”
mentioning
confidence: 99%